Contribuições da praxiologia motriz e dos estudos culturais para o ensino dos esportes na escola - Marques, Rodrigo Gonçalves Vieira (2024)
This study presents reflections based on Cultural Studies, the Cultural Curriculum, and their articulation with the knowledge of Motor Praxiology, in favor of the inclusive teaching of sociomotor sports such as handball, basketball, futsal, doubles tennis, rugby, and volleyball. The overall objective is to investigate how the articulation between the knowledge of Motor Praxiology and the principles of the Cultural Curriculum, anchored in Cultural Studies, can contribute to the teaching of school sports, with an emphasis on the inclusion of students historically excluded due to social markers of gender and ethnic-racial identity. It also identifies possible differences in practices that are closer to institutionalized sports games than to non-institutionalized sports games (reduced/simplified games). The research was qualitative, with characteristics of intervention research, and categorical content analysis was used. Thirty-three fifth-grade students from a private school in the interior of São Paulo participated. Questionnaires (open and closed), learning diaries, artistic production (drawings, timeline and reflective stickers) were used as resources to obtain the study data. The results indicated that sports games that most closely resembled institutionalized models generated lower participation and a greater sense of exclusion among students, especially when compared to non-institutionalized sports games (reduced/simplified games). When analyzing the data with a focus on Social Markers of gender and ethnic-racial identity, the non-institutionalized games, designed with intentional changes in their internal logic based on Motor Praxiology insights and in intersectional articulation with Cultural Curriculum principles, especially curricular justice, demonstrated potential for broadening student participation. Particularly noteworthy was the increased participation of girls, including Black and brown students, as well as a broader perception of inclusion in classes. The articulation of praxeological knowledge, Cultural Studies, and the principles of the Cultural Curriculum has proven to be a path that can be followed in Physical Education classes with transformative educational goals, as it values inclusive and reflective pedagogical practices in sports education at school. This approach can be explored beyond sports content to other motor practices.